Keselamatan dan Kesehatan Kerja di Industri Fast Fashion: Analisis Literatur Tentang Risiko dan Tantangan - Irma Fajriah (Lembaga Pengembangan Kinerja Dosen, 2025)
The fast fashion industry has become a dominant sector in the global economy, providing affordable fashion products and generating millions of jobs. However, behind its rapid growth, there are significant concerns regarding occupational safety and health (OSH), especially in developing countries that serve as major production hubs. Workers often face hazardous working conditions, exposure to toxic chemicals, excessive working hours, and a lack of adequate health protection. This study aims to analyze the main OSH risks and challenges in the fast fashion industry through a comprehensive literature review and comparative analysis of different countries, including Indonesia, Bangladesh, Vietnam, and China. The findings indicate that weak regulations, lack of enforcement, and high production pressures contribute to unsafe working conditions. Countries with stricter OSH policies, such as China, tend to have better compliance, whereas Indonesia and Bangladesh still struggle with poor implementation and monitoring. To improve OSH standards, this study recommends strengthening regulatory frameworks, enhancing worker safety training programs, increasing corporate accountability, and promoting ethical consumer behavior. Governments, companies, and consumers must collaborate to ensure a safer and more sustainable fast fashion industry.